Life Imprisonment in Asia - Zyl Smit, Dirk van; Appleton, Catherine; Vucong, Giao (Palgrave Advances in Criminology and Criminal Justice in Asia, 2023)
1. Japan- Life Imprisonment in Japan: The existing Legal System and Alternative Sanctions to the Death Penalty -- 2. China- Life Imprisonment in China: Law and Practice -- 3. India- Life Imprisonment in India: A Life Without Hope? -- 4. Hong Kong -- 5. South Korea- Life Imprisonment in South Korea: Law and Practice in the Shadow of the Death Penalty -- 6. Vietnam- Life Imprisonment and Human Rights: Reflections on the Vietnamese Context -- 7. Bangladesh- Ensuring a Constructive Prison Experience for Life Sentenced Prisoners in Bangladesh -- 8. Indonesia- Imposing and Enforcing Life Imprisonment in Indonesia -- 9. Malaysia- Reviewing Life Imprisonment in Malaysia: Prospects for Law Reform? -- 10. Singapore- Life Imprisonment in Singapore: Legal and Sociological Perspectives -- 11. Australia- Attempting to Restore a Right to Hope of Release to Life Imprisonment in Australia: The Phuong Ngo Case -- 12. New Zealand- Mapping Life Imprisonment and Indeterminate Sentencing in New Zealand -- 13. Conclusion- Asian Life Imprisonment in Worldwide Perspective. .